1992
DOI: 10.2307/2159792
|View full text |Cite
|
Sign up to set email alerts
|

On the Ideal Structure of the Nevanlinna Class

Abstract: Abstract.Let N denote the Nevanlinna class, i.e. the algebra of holomorphic functions of bounded characteristic in the open unit disc. We study analytic conditions for a finitely generated ideal to be equal to the whole algebra N. Then we characterize the finitely generated prime ideals containing a nontangential interpolating Blaschke product. Further, we give an example of an ideal of N whose closure in the natural metric on A' is not an ideal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Since |B * * 1 (α j )| ≤ |B * * 2 (α j )| and ρ(α * j , α j ) = |B * * 1 (α j )|/4, Schwarz' Lemma (see Lemma 2.1(a)) gives |B * * 2 (α * j )| ≥ |B * * 2 (α j )|/2 and |B * * 1 (α * j )| ≤ 3|B * * 1 (α j )|/2. Hence, using again Lemma 2.1(a) and (4.14), 16) where C 2 > 0 is an absolute constant. From (4.15) and (4.16) we get…”
Section: Case (I)-cmentioning
confidence: 83%
See 1 more Smart Citation
“…Since |B * * 1 (α j )| ≤ |B * * 2 (α j )| and ρ(α * j , α j ) = |B * * 1 (α j )|/4, Schwarz' Lemma (see Lemma 2.1(a)) gives |B * * 2 (α * j )| ≥ |B * * 2 (α j )|/2 and |B * * 1 (α * j )| ≤ 3|B * * 1 (α j )|/2. Hence, using again Lemma 2.1(a) and (4.14), 16) where C 2 > 0 is an absolute constant. From (4.15) and (4.16) we get…”
Section: Case (I)-cmentioning
confidence: 83%
“…For the Nevanlinna class R. Mortini observed that a well known result of T. Wolff implies the following corona theorem (see [17] or [16]).…”
Section: Introductionmentioning
confidence: 99%
“…has a harmonic majorant (the function H). Therefore, by (13), the map λ k −→ M k k ∈ ∪ j J j has no harmonic majorant. This is (b) in the statement.…”
Section: Proof Of Theorem Bmentioning
confidence: 99%
“…The Corona problem for the Nevanlinna class was solved by R. Mortini in [12, Satz 4] (see also [13]). Let Har + (D) denote the cone of positive functions in the unit disk.…”
mentioning
confidence: 99%
“…For the Nevanlinna class R. Mortini observed that a well-known result of T. Wolff implies the following corona theorem (see [32] or [26]). Theorem 5.2.…”
Section: Finitely Generated Idealsmentioning
confidence: 99%